1997
DOI: 10.1002/ana.410420303
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral activity pattern due to subthalamic nucleus or internal pallidum stimulation in Parkinson's disease

Abstract: Injection of apomorphine, a dopaminergic agonist drug, decreases akinesia and increases cortical activityThe main driving force for the increased discharge of cells in GPi and SNr is thought to be overactivity of bl.the subthalamic nucleus (STN), which has excitatory projections to both structures. As a result, both GPi and STN have been identified as potential targets for neurosurgical procedures aimed at reducing basal ganglia outputs [6-111. Pallidotomy has now been performed successfully by many groups [6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
250
4
11

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 453 publications
(288 citation statements)
references
References 33 publications
23
250
4
11
Order By: Relevance
“…Brain activity was reduced in the medial frontal motor areas, including the SMA, in parkinsonian patients compared with control subjects who showed an increased brain activity in these areas [20]. Another study using positron emission tomography in the PD patients with STN stimulation showed that a movement-related increase in brain activity during effective STN stimulation was higher in SMA, cingulate cortex and dorsolateral prefrontal cortex than during ineffective stimulation [28].…”
Section: Discussionmentioning
confidence: 98%
“…Brain activity was reduced in the medial frontal motor areas, including the SMA, in parkinsonian patients compared with control subjects who showed an increased brain activity in these areas [20]. Another study using positron emission tomography in the PD patients with STN stimulation showed that a movement-related increase in brain activity during effective STN stimulation was higher in SMA, cingulate cortex and dorsolateral prefrontal cortex than during ineffective stimulation [28].…”
Section: Discussionmentioning
confidence: 98%
“…In both of these cases, which we have not explored, our results suggest that the elimination of rhythmicity through DBS of STN would restore normal thalamic and cortical processing of sensorimotor inputs. While there is significant evidence that basal ganglia and cerebellar inputs to thalamus converge in cortical motor areas (Limousin et al, 1997;Hoover et al, 1999;Middleton et al, 2000;Bergman et al, 2002;Sestini et al, 2002), testing cortical responses to converging thalamic bursts induced by GPi, together with normal signals relayed from the cerebellum through other thalamic nuclei, remains an important step for future simulations and experiments.…”
Section: Discussionmentioning
confidence: 99%
“…144 Comparison of PET data on responses between STN HFS and GPi HFS suggested that clinically effective stimulation of both targets led to supplementary motor cortex and cingulate cortex activation during a joystick task. 146 STN HFS produced higher cortical activation in general, however, and especially over the dorsolateral prefrontal cortex (DLPFC). Indeed, anatomical tracings have shown that STN neurons project to SNr, which in turn target the DLPFC through the nigral-receiving area of thalamus.…”
Section: Why So Many Targets?mentioning
confidence: 99%